Relationship between the industry specialist auditors and financial reporting timeliness under MFRS - Puat Nelson, Sherliza; Ahmad, Maslina; Mohamed, Hamidah (UPM Press, 2019)
This paper aims to identify the association between financial reporting timeliness and the presence of industry specialist auditors. The auditor’s report lag (ARL) is used as a proxy for the financial reporting timeliness. The association between the two factors was examined through the resource dependence theory. Data comprise the 2012 annual reports of 796 Malaysian public listed companies and 342 of these companies had fully complied with the Malaysian Financial Reporting Standards (MFRS). From the results noted, it appears that financial reporting timeliness can be improved through the engagement of industry specialist auditors. This outcome contributes to the existing literature in auditing by enlarging the empirical evidence that was assessed with four different methods.